Synergisms in antioxidant and anti-hepatocellular carcinoma activities of artichoke, milk thistle and borututu syrups - Pereira, Carla (2014)
Artichoke, borututu and milk thistle are three medicinal plants well-known for their capacity to prevent oxidative stress and many liver diseases. In a previous work, we reported the bioactivity of infusions and pills based on these plants; herein, the aim was to provide scientific information about the antioxidant and anti-hepatocellular carcinoma activities of syrups based on these medicinal plants and evaluate the synergism among the combined plants by using syrups based on the mixed plants or prepared form the combinations of individual species. The antioxidant activity was measured by radical scavenging activity, reducing power and lipid peroxidation inhibition, while the anti-hepatocellular carcinoma activity and the hepatotoxicity were evaluated using HepG2 human cell line and a primary culture of porcine liver cells, respectively. Milk thistle syrup proved to have the highest antioxidant activity in all the assayed methods, providing the best results either in single syrup or included in mixed syrups. Synergistic effects were the main interactions observed in the mixture of artichoke, borututu and milk thistle; mixing the syrups based on each single plant proved to be more efficient regarding antioxidant proposals than mixing plants in the same syrup. The latter was advantageous for anti-hepatocellular carcinoma activity.